CFD Assessment of the Inhaled Air Quality in a UFAD-Conditioned Office with Personalized Ventilation - Kanaan, Mohamad; Gazo-Hanna, Eddie; Amine, Semaan (Engineering, Technology & Applied Science Research, 2025)
The quality of the inhaled air in an Underfloor Air Distribution (UFAD) system assisted by Personalized Ventilation (PV) is evaluated based on the CO2 concentration levels in the respiration zone. Also, whole-body thermal comfort is assessed using the Predicted Mean Vote (PMV) model. A comprehensive three-dimensional Computational Fluid Dynamics (CFD) model is developed to simulate the indoor airflow behavior, including the interactions between the PV jet, human exhaled flow, and thermal plume. A parametric study is carried out by varying the UFAD and PV flow rates to analyze their effects on the overall thermal comfort and inhaled air quality. The results indicate that, for the proposed configuration and terminal device, PV with a supply temperature of 24 oC and flow rates between 2.5 and 7.5 L/s may reduce the CO2 concentrations in the respiration zone by up to 34%, while ensuring the occupant comfort. However, this finding cannot be generalized to all PV situations, as the present study accounts only for normal human breathing and a constant heat flux density. The variations in these parameters may alter the outcome due to the different interactions of the PV airflow in the occupant’s microenvironment.